Performance appraisals and job satisfaction - Patrick Kampkötter (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Formal performance appraisals (PA) are one of the most important human resource management practices in companies. In this paper, we focus on the reaction of employees to these performance assessments. In particular, we investigate the effect between the incidence of being formally evaluated by a supervisor and job and income satisfaction. Building on a representative, longitudinal sample of more than 12,000 individuals from the German Socio-Economic Panel Study (SOEP), we apply fixed effects regressions and find a significantly positive effect of PA on job satisfaction, which is driven by appraisals that are linked to monetary outcomes. Furthermore, the moderating effects of personality traits (Big Five, locus of control) on the relationship between PA and job satisfaction are explored. We find a negative interaction term between PA without any monetary consequences and both employees scoring high on openness to experience and internal locus of control. This suggests that for these employees appraisals, which induce performance monitoring without any monetary consequences, have a detrimental effect on job satisfaction rates.
Keywords: 330; Performance Appraisal; Job Satisfaction; Income Satisfaction; Big Five; Locus of Control; SOEP